The Service Startup Model: A new model to support service entrepreneurship - Danilo Passos da Cruz (2021)
Entrepreneurs currently face the challenge of creating a successful startup that provides a desirable service to customers. Research about establishing a startup and about designing better services are available but are rarely considered together. This study aims to present a new model to support service entrepreneurship by understanding the synergies between Service Design and Entrepreneurship. This study relied on the DSR methodology, supported by individual semi- structured interviews with sixteen participants to understand the problem space. The interviews were conducted with entrepreneurs, designers, and business consultants from Brazil and Portugal. Data collected were qualitatively analyzed and codified using the NVivo software. Five stages of the development process (discover, define, develop, deliver and grow) and four main challenge groups (strategy, team, financial and personal) were identified and characterized as a contribution of this study. This research provides an iterative model, the Service Startup Model, that organizes crucial questions to be solved by entrepreneurs in different areas, such as problem vision, service concept vision, and growth vision, with culture values, resources, finances, and growth assumptions.